ASSESSMENT OF THE INTEGRATED CHITINASE GENE STABILITY IN WHEAT LINES AFTER BIOBALLISTIC TRANSFORMATION - Malakhova Natalya Petrovna; Skiba Yuriy Aleksandrovich; Maltseva Elina Romanovna; Iskakova Gulnur Ayupovna; Naizabayeva Dinara Adamzhankyzy; Tezekbaeva Botakoz Kulbaevna; Bissenbay Akerke Ongarbaykyzy; Toibayeva Karlygash Amirovna; Ismagulova Gulnara Akimzhanovna (Academic Journal of Physical and Chemical Sciences, 2020)
The synthesis of PR-proteins (pathogenesis related proteins), the most studied of which are chitinases and β-1,3-glucanases, occurs in response to infection with pathogens in plants. Information about the exact role of individual PR proteins within plant immunity makes it possible to use certain specific antifungal proteins for the development of transgenic plants with increased resistance to fungal diseases. At the same time, it is important not only to obtain a plant with the desired trait, but also to fix in it the stable expression of the transferred gene and the inheritance of the acquired trait in generations. Herein we have studied the stability of the chitinase gene insertion in T1, T2 and T3 generations of transformed wheat lines obtained by the method of cis-gene transfer. Primary transformed regenerant plants were obtained as a result of bioballistic transformation of the chitinase gene into immature wheat germ of Saratovskaya 29 and Kazakhstanskaya 19 varieties. Following screening of regenerant plants by PCR for the presence of the target gene made it possible to select 6 lines presumably carrying the insert based on variety Saratovskaya 29 and 2 lines based on variety Kazakhstanskaya 19. The seed material of the selected regenerant plants was cultivated in soil conditions and the seeds of the T1 generation were obtained. DNA amplification of 8 selected lines St-29№25, St -29№43, St-29№44, St-29№33, St-29№26, St-29№35, Кz-19№1, Кz-19№2 with specific primers revealed insert-carrying lines, partially cleaved lines and lines with a high degree of insert instability. According to the results of the T2 and T3 generations PCR analysis, a complete absence of insertion in the St-29№35 and St-29№33 lines was revealed, a partial cleavage of the trait in the St-29№43 and Kz-19№2 lines was revealed, and the stable inheritance of the chitinase gene in four lines St-29№25, St-29№44, St-29№26 and Kz-19№1.was confirmed. These lines were selected as promising for in-depth study of their resistance to fungal diseases and further replication.